Two Ways of Viewing Reality in Precarious Balance - Robbiano, Chiara (Peitho. Examina Antiqua, 2013)
Iain McGilchrist, The Master and His Emissary, The Divided Brain and the Making of the Western World, New Haven-London 2012 (prima stampa 2009).